2014
DOI: 10.3354/meps11026
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of diatoms to projected ocean changes

Abstract: With progressive future global change, marine phytoplankton in surface oceans will be subjected to ocean acidification, as well as to increased solar exposures and decreased vertical transport of nutrients from depth due to increasing stratification. We employed a simultaneous multivariate treatment approach to investigate the physiological and biochemical responses of the diatoms Thalassiosira pseudonana and Skeletonema costatum to these projected ocean changes. Diatoms were grown under different 'clustered' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Although the underling mechanism for explaining lower P:C at higher temperature is not fully understood, there are three hypotheses (Paul et al, 2015): (1) increase in metabolic stimulation of inorganic carbon uptake over phosphorus uptake; (2) increase in nutrient use efficiency which enables greater carbon fixation for given nutrient availability; and (3) "translation compensation theory," which predicts that less P-rich ribosomes are required for protein synthesis and growth as the translation process becomes kinetically more efficient (McKew et al, 2015;Toseland et al, 2013;Woods et al, 2003;Xu et al, 2014;Zhu et al, 2017). In this meta-analysis, the decrease in P:C in cyanobacteria at elevated temperatures (Fig.…”
Section: Temperaturementioning
confidence: 99%
“…Although the underling mechanism for explaining lower P:C at higher temperature is not fully understood, there are three hypotheses (Paul et al, 2015): (1) increase in metabolic stimulation of inorganic carbon uptake over phosphorus uptake; (2) increase in nutrient use efficiency which enables greater carbon fixation for given nutrient availability; and (3) "translation compensation theory," which predicts that less P-rich ribosomes are required for protein synthesis and growth as the translation process becomes kinetically more efficient (McKew et al, 2015;Toseland et al, 2013;Woods et al, 2003;Xu et al, 2014;Zhu et al, 2017). In this meta-analysis, the decrease in P:C in cyanobacteria at elevated temperatures (Fig.…”
Section: Temperaturementioning
confidence: 99%
“…Yet, in the diatom C. debilis, under dynamic light, elevated pCO 2 decreased primary production (Hoppe et al, 2015). Experiments on multiple stressors including not only pCO 2 and light, but also temperature, nutrients and iron, found that light increased growth, when nutrients were not limiting, while pCO 2 did not have any effect (Xu et al, 2014;Boyd et al, 2015a). There are great differences in the definition of high and potentially stressful irradiances that are used in studies investigating effects of constant irradiances in temperate and Antarctic phytoplankton species (125 to 380 µmol photons m −2 s −1 ; Kropuenske et al, 2010;Mills et al, 2010;Norici et al, 2011;Hoogstraten et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Increasing attention is devoted to the interplay between MEDs on phytoplankton under the projected climate change scenarios (Xu et al, 2014a;Boyd et al, 2015;Flynn et al, 2015). To date, studies have focused on two concurrent variables (Rhee and Gotham, 1981;Staehr and Sand-Jensen, 2006;Sommer et al, 2015), while a few have examined three-way (Feng et al, 2008;Shi et al, 2015) or multi-way interactive effects of environmental factors (Xu et al, 2014b;Brennan and Collins, 2015).…”
mentioning
confidence: 99%